Peningkatan Hasil Belajar Kimia melalui Model IBL (Inquiry Based Learning) pada Siswa Kelas XII MIPA 3 SMA Negeri 1 Sutojayan - Yasin, M. (Jurnal Simki Postgraduate, 2023)
Based on the results of observations and interviews conducted at SMA Negeri 1 Sutojayan, it turns out that the results of studying chemistry for class 25% of this is because learning is dominated by teacher-centred lecture methods. The aim of this research is to determine the improvement in student chemistry learning outcomes using the IBL learning model. This research is classroom action research carried out in three cycles. Each cycle consists of planning, implementation, observation and reflection. The subjects of this research were class XII MIPA 3 students at SMA Negeri 1 Sutojayan. The focus examined in this research is student learning outcomes. Cognitive learning outcome data was obtained from test scores at the end of the cycle, affective learning outcome data was obtained from student questionnaires, while psychomotor learning outcome data was obtained from observation results. From the research results, the average cognitive learning outcomes in cycle I increased from 58.19 (pre-action value above KKM) or around 25% (pre-action value above KKM) to 69.58 (cycle I value above KKM) or around 53% (cycle I). In cycle II it reached 85.55 (cycle II value above KKM) or around 100%. Meanwhile, the average learning process and attitude results in cycles I and II respectively were 78.24;78.54 and 93.52;97.37. Based on the results of this research, it can be concluded that student learning outcomes can be improved through the application of the learning model with the IBL approach.